An Analysis of The Politeness Strategy used in Mata Najwa Talk Show on Trans7 - Dwi Handayani Silitonga (English Education Department at FKIP Nommensen University, 2022)
This study aimed to describe the Politeness Strategies used in Mata Najwa Talk Show. This study applied a qualitative research design to explore the politeness strategies used by the participants in Mata Najwa Talk Show in their interactions. The participants in this study were Najwa Shihab as a host, Erick Thohir and Nadiem Makarim as guests. The data in this study were in the form of utterances that contain politeness strategies. The result showed that the host not only use Positive Strategy to reveal the guests’ issue but also use a Negative strategy to reduce the interference with the guests’ freedom of action. The guests tend to use Positive Politeness because they tried to convince society about their new policies and state that they share the same specific wants, goals, or values, namely a better condition for this country. From the analysis, the researcher found out the result that Positive politeness (76,32%), Negative Politeness (18,42%) and off Record Strategy (5,27%) and there is no Bald Record Strategy used in this analysis.